2010
DOI: 10.1118/1.3302916
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional quantitative evaluation method of nonrigid registration algorithms for adaptive radiotherapy

Abstract: Purpose: Current radiotherapy is progressing to the concept of adaptive radiotherapy, which implies the adaptation of planning along the treatment course. Nonrigid registration is an essential image processing tool for adaptive radiotherapy and image guided radiotherapy, and the threedimensional (3D) nature of the current radiotherapy techniques requires a 3D quantification of the registration error that existing evaluation methods do not cover appropriately. The authors present a method for 3D evaluation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…In this scenario, characterized by low image contrast, the regularization term of the algorithms failed to preserve the anatomy of the ROIs adjacent to the bladder, extending the deformation well beyond its support. Accuracy values proximal to the more reliable situation depicted by DVF1 have been found in mono‐institutional studies on self‐made software …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In this scenario, characterized by low image contrast, the regularization term of the algorithms failed to preserve the anatomy of the ROIs adjacent to the bladder, extending the deformation well beyond its support. Accuracy values proximal to the more reliable situation depicted by DVF1 have been found in mono‐institutional studies on self‐made software …”
Section: Discussionmentioning
confidence: 85%
“…In recent years, DIR has been extensively implemented in multiple RT applications: contour propagation, dose summation in IGART, [33][34][35][36] organ motion modeling on 4D scans 26,27,37 and multimodal image registration. 38,39 Although many commercial platforms are available, there is a lack of solid methods to provide DIR QA, resulting in fuzzy knowledge concerning the accuracy and reproducibility of these systems in typical clinical settings.…”
Section: A Dir Data Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Previous works have indicated that a DSC > 0.7 shows a satisfactory overlapping between two volumes 5, 23, 24 and the same value was used in the case of OVI. 14 Furthermore, the evaluation method previously proposed by the authors 25 is applied to the contours of the prostate to determine the influence of a better registration of the rectum in the automatic delineation of the prostate. This methodology allows the representation of the spatial distribution of the error around the reference prostate, showing the delineation variability with respect to the relative position on the prostate.…”
Section: Iic Evaluationmentioning
confidence: 99%
“…This methodology allows the representation of the spatial distribution of the error around the reference prostate, showing the delineation variability with respect to the relative position on the prostate. 5,25…”
Section: Iic Evaluationmentioning
confidence: 99%